Delineation of the selected Cucumis L. species and accessions using leaf architecture characters (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Masungsong LA, Belarmino MM, Buot IEJr. 2019. Delineation of the selected Cucumis L. species and accessions using leaf architecture characters. Biodiversitas 20: 629-635. Regardless of the several attempts of the early and recent studies to separate the wild species of Cucumis from the cultivated ones, there is still taxonomic confusion brought about by the similarities in morphology of the genus. In a gene bank with so many species and accessions of Cucumis stored, it is appropriate to delineate these numerous accessions to save time and resources as well. This study aims to delineate fifty selected Cucumis accessions based on leaf architecture. Using Unweighted Pair Group Method using Averages (UPGMA) and Euclidean distance coefficient, a cluster analysis for the fifty Cucumis accessions was done. A dendogram with cophenetic coefficient of 0.9606 supported the clustering of the Cucumis species and accessions. At Eucledian distance of 1.5 two major clusters were formed on the basis of secondary vein spacing. Cucumis melo accessions separated from all the remaining accessions of C. myriocarpus, C. metuliferus, C. anguria and C. anguria var longaculeatus for having an increasing towards the base secondary vein spacing while the rest have irregular pattern of secondary vein spacing. Further sub-clustering of the remaining accessions comprising four species were delineated on the basis of tertiary vein (C. myriocarpus), tertiary vein angle to primary (C. metuliferus), and blade class (C. anguria and C. anguria var longaculeatus). Laminar shape delineated C. myriocarpus accessions from each other, apex angle for C. metuliferus accessions, and primary vein size for C. melo accessions. Results implied that leaf architecture is a good tool to classify the numerous accessions of Cucumis.